Amelioration of electrochemical and photovoltaic performances on P(VP‐co‐VAc) based gel polymer electrolyte by incorporating double salt for dye‐sensitized solar cells. Issue 33 (18th May 2016) - Robin, S.; Ng, H. M.; Ramesh, S.; Ramesh, K.
ABSTRACT: Dye‐sensitized solar cell (DSSC) is an alternative photovoltaic application used to replace the liquid electrolyte dependent conventional photovoltaic cell. In this research, gel polymer electrolyte (GPE) was used to replace the unstable liquid electrolyte. This GPE consists of poly[1‐vinylpyrrolidone‐co‐vinyl acetate] (P[VP‐ co ‐VAc]), tetrabutylammonium iodide (TBAI), sodium iodide (NaI), iodine (I2 ), ethylene carbonate (EC), and propylene carbonate (PC). The GPE was tested for its ionic conductivity and an optimum level was reached at sample with 30% TBAI and 6% NaI at 1.17 × 10 −3 S cm −1 . The DSSC was then fabricated with all GPEs and a photovoltaic performance study was conducted. As a result, the highest photovoltaic conversion efficiency (PCE), η for a single salt was 3.04% for 40% TBAI. When a second salt is added, the system showed improvement in efficiency, η to 4.54% with short circuit current density, J sc of 11.02 mA cm −2 and open circuit voltage, V oc of 0.67 V and FF of 61%. The other changes after the addition of TBAI and NaI salts have been observed through X‐ray diffraction, Fourier transformation and thermal analysis studies. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43805. Abstract :